2015
DOI: 10.1287/serv.2015.0097
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of New Service Development: Case Video-Supported Home Care Service

Abstract: I n all developed economies, there is a mounting demand for effective solutions to elderly care stemming from an aging population and the high cost of resources needed. Hence, significant investments have been made in developed countries to stimulate the growth of information and communication technology-enhanced services for the home care markets. However, digital provisioning of home care services includes major challenges. This study uses an individual longitudinal case study that explores the collaborative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 74 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…On the one hand, many of the papers relate to previous research without using concrete and established theories. Examples of this approach are theoretical backgrounds on service innovation (Yang and Hsiao 2009), new service development (Lin and Hsieh 2014;Wallin et al 2015), or the cocreation of value (Komulainen et al 2007;Villarroel Ordenes et al 2014). This approach was chosen in 15 of the 37 papers.…”
Section: Total 37mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, many of the papers relate to previous research without using concrete and established theories. Examples of this approach are theoretical backgrounds on service innovation (Yang and Hsiao 2009), new service development (Lin and Hsieh 2014;Wallin et al 2015), or the cocreation of value (Komulainen et al 2007;Villarroel Ordenes et al 2014). This approach was chosen in 15 of the 37 papers.…”
Section: Total 37mentioning
confidence: 99%
“…Based on an example of RFID use, they showed that personality traits such as technology anxiety and privacy concerns affect the attitude toward the use of such systems on a technology and system level. Considering other important factors on the individual level, Wallin et al (2015) pointed out the importance of analyzing the contextual value for a variety of relevant stakeholders and of identifying the key persons. Burke (2002) investigated aspects of experience that are important for beneficiaries of the ICT-enabled shopping system.…”
Section: Thematic Findingsmentioning
confidence: 99%
“…To date, the operations management literature on home health has been primarily focused on nurse scheduling and routing (Begur et al 1997, Cappanera and Scutellà 2015, Eveborn et al 2009. A recent paper by Wallin et al (2015) has employed a case study method to explore the use of telemedicine in home care. We extend this stream of work by using operational data from home health providers to understand how home health care providers may affect hospital readmissions.…”
Section: Introductionmentioning
confidence: 99%